Concavity-enhanced chiral self-assembly of anisotropic nanoparticles toward strong chiroptical activity - Jiayi Zhou; Yuzhe Gao; Deyi Zhang; Kexin Ren; Mengqi Dai; Huan Wang; Limin Qi (Nature Communications)
Abstract Chiral plasmonic nanomaterials have attracted significant attention due to their fascinating chiroptical properties and promising applications including chiral sensing, asymmetric catalysis, biomedicine, and chiroptics. Self-assembly of plasmonic nanoparticles is promising for constructing chiroplasmonic nanomaterials, but it remains challenging to obtain homochiral assemblies with high optical asymmetry. Here, gold nanodumbbells featuring a concave morphology are employed as achiral building blocks for controllable self-assembly into stable homochiral assemblies exhibiting strong chiroptical activity. The formation of helically stacked side-by-side assemblies with right handedness is triggered by introducing bovine serum albumin as the chiral additive. Remarkably, an asymmetry factor as high as 0.23 is obtained for the chiral assemblies. It is revealed that the concavity of the nanodumbbells considerably enhances the chirality and stability of the assemblies. Furthermore, the chiral assemblies are utilized as hosts for achiral fluorescent species to generate circular polarization luminescence. This work may advance the structural design of building blocks for chiral assembly toward novel chiroplasmonic nanomaterials.